PARAMETER OPTIMIZATION OF JC CONSTITUTIVE MODEL OF AL7050 ALLOY BASED ON OXLEY’S THEORY - WANG Yun; ZHANG ChangMing; ZHANG Yu (Jixie qiangdu)
Aiming at the problem that Al7050 alloy is easy to deform in cutting process,the JC constitutive model suitable for practical cutting is established. Based on Oxley’s theory,a solution model was established. The JC constitutive model parameters of Al7050 alloy were obtained by using genetic algorithm and experimental data,and the JC constitutive model was verified by using cutting force as evaluation index. The results show that the strain range of JC constitutive model is 0. 80 ～ 1. 01,the strain rate range is 1. 6 × 10~3 s-1～ 2 × 10~4 s-1,and the temperature range is 96. 48 ℃ ～ 213. 07 ℃ . The average errors of the simulation and test values of the main cutting force and feed force using the custom material model are 4. 79% and 16. 08%,respectively. The average errors of the simulation and test values of the main cutting force and feed force of the material model with the software are 15. 08% and 25. 97% respectively,and the conclusion that the simulation value of the cutting force with the custom material model is more consistent with the test result is drawn.